Enhancement mechanisms of Tm3+-codoping on 2 μm emission in Ho3+ doped fluoroindate glasses under 888 nm laser excitation. Issue 5 (1st April 2020) - Wang, Ruicong; Zhao, Haiyan; Zhang, Meng; Zhang, Jiquan; Jia, Shijie; Zhang, Jun; Peng, Hangyu; Brambilla, Gilberto; Wang, Shunbin; Wang, Pengfei
Abstract: Ho 3+ doped and Ho 3+ /Tm 3+ co-doped fluoroindate glass samples were prepared and their emission properties were compared. Under 888 nm laser excitation, the emission at 2 μm of Ho 3+ ions with co-doping 2 mol% Tm 3+ ions had a 2.9-fold improvement compared with that of Ho 3+ doped. The absorption and emission spectra, and energy level lifetime of Ho 3+ /Tm 3+ co-doped glass samples were measured to analyze the energy transfer processes and enhancement mechanisms. The luminescence intensity at 2 μm can be greatly increased due to the bidirectional energy transfer between Tm 3+ and Ho 3+ ions.